Adapting to Uncertainty: A Mixed-Method Study on the Effects of the COVID-19 Pandemic on Expectant and Postpartum Women and Men - Tavares, Inês M.; Fernandes, Joana; Moura, Catarina V.; Nobre, Pedro J.; Carrito, Mariana L. (Frontiers in Psychology, 2021)
Detrimental biopsychosocial effects of the COVID-19 pandemic on populations have been established worldwide. Despite research indicating that the transition to parenthood is a vulnerable period for maternal and paternal health, an in-depth examination of the specific challenges the pandemic poses for new mothers and fathers is still lacking. Using a mixed-method design, we investigated individual and relational well-being of women and men who were expecting their first child during the first months of the COVID-19 pandemic in Portugal and its associations with contextual, individual, and relational factors. Adults older than 18 (n = 316, 198 women) from early pregnancy to 6-months postpartum completed a cross-sectional online survey assessing sociodemographic, individual (depression, anxiety, perceived stress), and relational (dyadic adjustment, perceived social support) self-report measures. From those, 99 participants (64 women) responded to an open-ended question and reported perceived changes in their couple’s relationship due to the pandemic. Men responding during strict lockdown measures reported significantly higher levels of perceived stress relative to those men who were not under lockdown. Overall, women reported higher levels of depression and greater social support than men. Qualitative analyses resulted in two main themes: Individual Changes and Relational Changes. These themes aggregate personal concerns and experiences (e.g., worsening of mental health, uncertainty about the future, lack of freedom) interrelated with relational issues (e.g., increased togetherness, avoidance of physical contact, and increased availability for parenthood during lockdown). The prevalence of negative effects (58.6%) exceeded the described positive effects (28.3%), and 13.1% described both positive and negative effects of the pandemic. Current findings offer grounds for important evidence-based strategies to mitigate the potential adverse effects of the current pandemic on new mothers’ and fathers’ individual and relational well-being.